Melanotic Neuroectodermal Tumor of Infancy: A Rare Case Report - Kumar, Kishore S.; Naleer, Mohamed H.; Visweswaran, Vivek; Krishnamurthy, Ganesh (Asian Journal of Neurosurgery, 2022)
Melanotic neuroectodermal tumor of infancy (MNTI) is a rare, pigmented tumor. It is a locally aggressive neoplasm of neural crest origin with a high recurrence rate. It occurs in craniofacial sites in more than 90% of cases and most commonly in the maxilla. It may also occur in epididymis, testis, ovaries, soft tissue, and bones of the extremities. It occurs in infants younger than 1 year of age with a slight male preponderance. We report a rare case of a child presenting with midline frontal pigmented MNTI.
Keywords: melanotic neuroectodermal tumor of infancy; congenital melanocarcinoma; superior sagittal sinus